On the Criticism of Conspirology Theories - Gasparyan, Vahagn (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The article highlights the importance of the study of conspiracy culture. The author of the article notes the wide dissemination of conspirology theories and substantiates the relevance of this topic, including in the framework of the velvet revolution in Armenia. The main critical lines of social and humanitarian sciences are discussed against conspirology theories and their shortcomings are revealed. The author shows the onesidedness and the invalidity of that criticism and tries to substantiate the uniqueness of the problem of conspirology theories and the need for new, innovative and empirical based studies on conspirology culture.